History of the Tatar community of Semipalatinsk - Pavel S. Shablei (Историческая этнология, 2020)
The history of the Tatar community of Semipalatinsk is examined in the article. Particular attention is paid to the functioning of Tatar mosques, educational institutions, the development of Muslim charity, and Sufism. Despite the fact that the population of Semipalatinsk had a mixed ethnic structure, up to the early twentieth century, Tatars constituted almost a quarter of it. Tatar merchants set priorities for the development of the local economy, and students from various regions of the Russian Empire studied at madrasas. In addition, Semipalatinsk was the largest center of the Muslim culture in the Eastern part of modern Kazakhstan.